Leveraging AI and ICT for Greener Education in the Face of Climate Change in Smart Classrooms - Doris Chasokela; Joseph Hlongwane (Journal of Research in Mathematics, Science, and Technology Education, 2025)
Artificial Intelligence (AI) and Information and Communication Technology (ICT) are reshaping educational approaches to sustainability and climate action, fostering environmentally responsible attitudes among students. The study seeks to find how the integration of Artificial Intelligence and Information and Communication Technology in Higher Education Institutions (HEIs) affects the promotion of sustainability and climate action among students and the extent to which these technologies enhance student engagement with sustainability concepts, facilitate diverse perspectives on climate issues and contribute to the overall reduction of the carbon footprint of educational institutions. Many academic institutions struggle to effectively integrate these technologies into their curricula, which may hinder the potential to engage students in meaningful ways regarding sustainability and climate action. Educators can personalise learning by utilising AI-driven analytics and ICT tools, making sustainability concepts more engaging. AI can assess learning patterns to deliver tailored content that highlights environmental stewardship, while ICT provides access to global resources, allowing students to explore climate issues from diverse perspectives. Smart technologies like IoT devices and virtual learning platforms are crucial for reducing the carbon footprint of educational institutions. Online learning minimises the need for physical infrastructure, reducing travel-related carbon footprints. By incorporating these technologies into curricula, institutions can cultivate a generation of informed, environmentally-conscious citizens. This study employs a qualitative approach to evaluate AI and ICT’s impact on promoting sustainability in university education. Data were collected through interviews with students and lecturers. Students reported increased engagement through AI-enhanced platforms. Lecturers indicated that the universities that use IoT energy monitoring reduce energy consumption. Recommendations include investing in lecturer training for AI and ICT integration, developing interdisciplinary curricula focused on sustainability, improving IoT infrastructure for energy management, encouraging cross-departmental collaboration on climate issues, and promoting student participation in sustainability-focused research projects. These steps can significantly enhance educational strategies and foster student commitment to climate action.